Flexural Behavior of Posttensioned Flat Plates Depending on Tendon Layout - Min Sook Kim; Young Hak Lee (Advances in Materials Science and Engineering)
This paper discusses the experimental results on the flexural behavior and deflections of posttensioned concrete flat plates depending on tendon layout. One reinforced concrete flat plate and two posttensioned concrete flat plates were manufactured and tested. One-way posttensioning layout and two-way posttensioning layout were considered in this paper. The load-deflection behavior and modes of crack are presented from the test results. Posttension systems effectively controlled crack and deflection. One-way and two-way posttensioning layouts both showed similar maximum load. However, serviceability improved with two-way posttensioning layout compared to one-way posttensioning layout. Also, the yield-line theory was applied to predict the ultimate load for the posttensioned flat plates. The comparison between the test results and estimation by yield-line analysis generally showed good agreement.